2018
DOI: 10.1002/gps.5027
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of effective support for homecare workers providing care to people with dementia at end of life

Abstract: Objective The aim of this study was to enhance understanding about homecare workers providing care to people with dementia at end of life by exploring homecare workers' perceptions of challenges and the support they needed and sometimes received. Methods Qualitative semi‐structured interviews were conducted with 29 homecare workers and 13 homecare managers in England. Framework analysis was used to analyse the data. Findings Four overarching challenges were identified: working with clients with dementia, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…10, Details of the search results and exclusion of studies can be found in Figure 1. eight qualitative, 34,42,50,51,54,57,59,60 five randomised controlled trials, 29,37,43,47,55 and four evaluation designs. 30,31,33,48 The remaining three studies used mixed-methods 10,41 and quasi-experimental designs.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10, Details of the search results and exclusion of studies can be found in Figure 1. eight qualitative, 34,42,50,51,54,57,59,60 five randomised controlled trials, 29,37,43,47,55 and four evaluation designs. 30,31,33,48 The remaining three studies used mixed-methods 10,41 and quasi-experimental designs.…”
Section: Search Resultsmentioning
confidence: 99%
“…3033,47,52,55 Hospice and home settings were the focus only in one study each. 46,59 Two studies were conducted in a combination of care settings, where one study was in home and nursing home settings, 10 and another included hospital and nursing home settings. 56 The care setting did not influence how end of life in dementia was defined.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first review to explore how observational research can inform our understanding of the experiences and quality of care delivered by home‐care workers. While qualitative interviews and focus group methods have been used frequently to study home care (Barken, Denton, Plenderleith, Zeytinoglu, & Brookman, ; Lovelock & Martin, ; Yeh, Samsi, Vandrevala, & Manthorpe, ), methods of observation have to date been used less widely. From the studies we reviewed, the researchers observed various home‐care practices that were in line with good‐quality care, defined as care that was consistent, and enabled the development of trusting relationships between the home‐care providers and recipients (Cabana & Jee, ; Denton et al, ; Olsson & Ingvad, ; Saultz & Lochner, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first review to explore how observational research can inform our understanding of the experiences and quality of care delivered by home-care workers. While qualitative interviews and focus group methods have been used frequently to study home care Lovelock & Martin, 2016;Yeh, Samsi, Vandrevala, & Manthorpe, 2019), methods of observation have to date been used less widely.…”
Section: Discussionmentioning
confidence: 99%
“…Vandrevala et al , 2016) and the home care industry ( e.g. Yeh et al , 2018). However, the live-in carer's living arrangement of residing in the place of work makes it a different context to allow direct comparison.…”
Section: Introductionmentioning
confidence: 99%